POLRI's Efforts to Address Sexual Violence Against Children - Stella Marsha (LEGAL BRIEF, 2019)
The rise of crimes that often occur in the community that makes sadness, namely sexual violence that occurs a lot in children is proven by based on statistical data from the UPTD P2TP2A Lampung Province which shows a significant increase in sexual violence against children within one year. The problem in this research is how is the effort of the National Police in tackling sexual violence against children? and what is the obstacle factor for the National Police in its efforts to combat sexual violence against children? This study uses a normative juridical approach and empirical jurisdiction. The informants of the study were the Tanjung Karang Timur Police Investigator, the UPTD P2TP2A Team in Lampung Province and the Lecturer in the Criminal Law Section of the Faculty of Law, University of Lampung. Based on the results of the research at the Tanjung Karang Timur Sector Police, the National Police's efforts in tackling sexual violence against children were first through Pre-eminent efforts, namely socialization of the community and children to prevent sexual violence that was rampant in children, both Preventive efforts carried out by officers with routine activities the police for prevention efforts are by carrying out patrols and hunting activities, the three repressive efforts, which are carried out by the police by giving strict sanctions to the perpetrators and providing guidance to the perpetrators while serving the sentence. The inhibiting factor is that the low awareness of the community to be involved in efforts to maintain and maintain Kamtibmas can be a trigger for the rise of criminal cases in the community.